Effect of long-acting antipsychotic treatment on psychiatric hospitalization rate in early psychosis patients: a naturalistic study - Raúl Sancho-Echeverria; Claudia Aymerich; José Manuel Rodríguez-Sánchez; Patxi Gil; Borja Pedruzo; Miguel Ángel González-Torres; Paolo Fusar-Poli; Celso Arango; Ana Catalan (SAGE Publishing, 2024)
Background: The effectiveness of long-acting injectable (LAI) antipsychotics in preventing relapses of first-episode psychosis is currently debated. Objectives: The study aimed to investigate the number of psychiatric hospitalizations comparing the LAI cohort versus the oral cohort during different phases of the illness, pre-LAI treatment, during LAI treatment, and after LAI treatment. Design: A naturalistic study was conducted on two independent cohorts of early psychosis patients receiving treatment from a specific early intervention service. The first cohort comprised 228 patients who received LAIs, while the second cohort comprised 667 patients who had never received LAIs. Methods: This study was designed as a longitudinal observational study conducted within a naturalistic clinical setting in two cohorts of early psychosis patients. Repeated series ANCOVA (ANCOVA-r) was used to study the number of hospitalizations in the different study periods (T1 = from the date of the first psychiatric record to the beginning of the mirror period; T2 = the mirror period; T3 = from the LAI implementation to the LAI discontinuation; and T4 = from the LAI discontinuation to the end). In all cases, discontinuation of LAI involved the return to oral treatment. In all, 35 patients had not T4 as they were still on LAI treatment at the time of database closing (September 2020), and their data were not included in the analysis of the effect of the LAI discontinuation. Results: The patients in the LAI cohort were younger, more frequently males, presented more schizophrenia diagnoses, and had a higher number of hospitalizations (2.50 ± 2.61 versus 1.19 ± 1.69; p  < 0.001) than the oral cohort. The number of hospitalizations at the end of the follow-up was higher in the LAI cohort [0.20 (standard deviation (SD)) = 0.79] versus 0.45 [SD = 0.45 (SD = 1.13); F (23.90), p  < 0.001]. However, after the introduction of LAIs, the differences in hospitalization rates between the two cohorts became less pronounced. Once LAI treatment was ceased, the hospitalization rate increased again. Conclusion: In our study, early psychosis patients receiving LAIs experienced a greater decrease in hospitalizations after introducing the LAI treatment than those treated solely with oral medication. These findings support using LAIs as a viable strategy for preventing rehospitalization and improving the overall course of treatment for individuals with early psychosis.